Interactions among moderate/severe periodontitis, ADIPOQ-rs1501299, and LEPR-rs1137100 polymorphisms on the risk of type 2 diabetes in a Chinese population. (July 2019) - Cao, Xiaojing; Huo, Pengcheng; Li, Wenjing; Li, Peng; He, Lu; Meng, Huanxin
Highlights: The risk of T2DM was higher in moderate/severe periodontitis. Rs1501299 GG genotype and rs1137100 GG genotype increase the risk of T2DM. The model shows a significant interaction among periodontitis and polymorphisms. Abstract: Objective: Type 2 diabetes mellitus (T2DM) is a complex disease influenced by genes and the environment. Periodontitis a demonstrated risk factor of T2DM. Previous studies related to gene-environment interactions on the risk of T2DM mainly focused on gene-obesity interactions. However, the impact of gene-periodontitis interaction on the risk of T2DM has not yet been investigated. This study aimed to investigate gene-environment interactions among moderate/severe periodontitis, polymorphisms of adiponectin (ADIPOQ)-rs1501299, and leptin receptor (LEPR)-rs1137100 on T2DM risk in Chinese subjects. Design: A case-control study was conducted in 239 Chinese participants from Beijing Hypertension Association Institute (BHAL). After full-mouth periodontal examinations, the participants underwent bilateral buccal swabs for DNA testing. ADIPOQ-rs1501299 and LEPR-rs1137100 were used for genotyping. Generalised multifactor dimensionality reduction (GMDR) and logistic regression were used to examine the interactions among single nucleotide polymorphisms (SNPs) and moderate/severe periodontitis on the risk of T2DM. Results: The risk of T2DM was higher in moderate/severe periodontitis [adjusted odds ratio (AOR) = 3.67, 95% confidence interval (95%CI): 1.26–10.71] in ADIPOQ-rs1501299 GG genotype (AOR = 3.42, 95%CI: 1.81–6.46) and LEPR-rs1137100 GG genotype (AOR = 3.16, 95%CI: 1.56–6.39). The GMDR model indicated that there was a significant three-factor model ( p = 0.001) involving rs1501299, rs1137100, and moderate/severe periodontitis, demonstrating a potential gene-environment interaction among periodontitis, polymorphisms of rs1501299, and rs1137100 influencing the risk of T2DM. Moderate/severe periodontitis patients with rs1501299-GG and rs1137100-GG have the highest T2DM risk after adjusting for age, gender, BMI, WHR, smoking status, alcohol consumption, economic status, and hypertension (AOR = 20.39, 95%CI: 2.64–157.26). Conclusions: Interactions among moderate/severe periodontitis, rs1501299-GG, and rs1137100-GG were associated with an increased risk of T2DM. This study may provide a new insight into the effect of gene-environment interactions on T2DM.